Removal of Copper (II) Ions from Polluted Water Using Modified Wheat Bran - Lomoko Gideon Masedi Nii Ayi (Sciendo, 2021)
The discharge of wastewater containing heavy metals into waterbodies is a major environmental issue that can influence the quality of the water supply; therefore, it is important to remove the pollutants dangerous to living organisms. The adsorption of copper (II) ions on modified wheat bran was investigated with respect to initial solution pH (2.0-7.0), contact time (5–120 min), adsorbent mass (0.5 g and 1.0 g), and initial metal ion concentration (2.0–20 mg/L). The optimum adsorption conditions were found to be at pH 5.0 and a contact time of 60 min with an adsorbent mass of 1.0 g where the maximum efficiency was recorded as 84.5 %. The adsorption uptake (in mg/g) of copper (II) ions slowly reached equilibrium in around 30 min and this amount was 0.30 mg/g using an adsorbent mass of 0.5 g. The adsorption uptake of copper (II) ions decreased with increasing mass of adsorbent and the adsorption efficiency (in %) increased with increasing mass of adsorbent. The experimental results were described using the Langmuir and Freundlich models, with the Langmuir model fitting better than the Freundlich model. The maximum modelled adsorption capacity was 4.24 mg/g and the modelled specific surface area of modified wheat bran was 6.36 m2. It was observed that the adsorption of copper (II) ions on modified wheat bran is efficient and suitable, therefore modified wheat bran is a relatively good adsorbent for the removal of copper (II) ions from polluted water compared to other agricultural adsorbents.